Zimbabwe, Ten Years of Independent Development. A General Overview - Vandermeulen, Martine (Afrika Focus, 1990)
It will be obvious from my face that I feel very proud to welcome you at this seminar. I am pleased to see that we are so many to be interested in Zimbabwe, but I also feel embarrassed. Ten minutes to portray ten years of independent development of a country, one minute for each year, seems a bit unfair towards that country and its people. Especially, if we want to take into account the fact that it is located in the troubled region of Southern Africa and of the high expectations that both the local and international community might have had after more than ten years of liberation struggle. You will understand that the scope of my presentation can only be limited and general, and I hope that you will accept my apologies for these important issues which I will not be able to mention during this short presentation.